Sleep and circadian rhythm disturbance in bipolar disorder. Issue 9 (8th February 2017) - Bradley, A. J.; Webb-Mitchell, R.; Hazu, A.; Slater, N.; Middleton, B.; Gallagher, P.; McAllister-Williams, H.; Anderson, K. N.
Abstract : Background: Subjective reports of insomnia and hypersomnia are common in bipolar disorder (BD). It is unclear to what extent these relate to underlying circadian rhythm disturbance (CRD). In this study we aimed to objectively assess sleep and circadian rhythm in a cohort of patients with BD compared to matched controls. Method: Forty-six patients with BD and 42 controls had comprehensive sleep/circadian rhythm assessment with respiratory sleep studies, prolonged accelerometry over 3 weeks, sleep questionnaires and diaries, melatonin levels, alongside mood, psychosocial functioning and quality of life (QoL) questionnaires. Results: Twenty-three (50%) patients with BD had abnormal sleep, of whom 12 (52%) had CRD and 29% had obstructive sleep apnoea. Patients with abnormal sleep had lower 24-h melatonin secretion compared to controls and patients with normal sleep. Abnormal sleep/CRD in BD was associated with impaired functioning and worse QoL. Conclusions: BD is associated with high rates of abnormal sleep and CRD. The association between these disorders, mood and functioning, and the direction of causality, warrants further investigation.